Faktor Faktor yang Mempengaruhi Psikologis Remaja di Masa Pandemi Covid-19 Kelas 7-8 di SMP Negeri 1 Naman Teran Tahun 2021 - Yuleen Natasya Telaumbanua; Lindawati Simorangkir; Imelda Derang (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Psychology is part of the science of human psychology that can affect a person's life in his daily life. Factors that affect the psychology of adolescents during this pandemic are the implementation of social distancing, online learning, and the fear of contracting COVID-19. Residents between the ages of 10 and 24 are considered adolescents. The study was to find out what are the factors that affect the psychology of adolescents during the COVID-19 pandemic in class VII and class VIII at SMP Negeri 1 Naman Teran ini2021. The research method used was a descriptive research design with a total of 75 respondents. The sampling technique used was the purposive sampling technique. The results showed that the majority of students due to stress factors for the implementation of social distancing were 69 people (92.0%), the majority of students due to stress factors were online learning asimanyiasi58 people (77.3%), and the majority of students due to fear of contracting covid. -19 with mild category as many as 64 people (85.3%). This shows that the factors of implementing social distancing, online learning and the fear of contracting COVID-19 affect the psychology of the students of SMP Negeri 1 Naman Teran. It is hoped that as information and material increase their knowledge students / I further increase their knowledge about the dangers of COVID-19 transmission